2016
DOI: 10.21836/pem20160206
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary nerve block within the pterygopalatine fossa of the horse with different volumes: practicability, efficacy and side-effects

Abstract: Summary:The maxillary nerve block within the pterygopalatine fossa is a commonly used technique in equine dental surgery. The objective of the present study was to determine the risks of the maxillary nerve block within the pterygopalatine fossa using two different doses of lidocaine and to evaluate methods for testing adequate analgesia of teeth and gingiva. In a preliminary experiment ten horses were trained to tolerate a mouth gag without sedation. A mechanical and thermal stimulation was applied on the pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
3
4
1
Order By: Relevance
“…Desensitizing the maxillary branch of the trigeminal nerve is useful for surgical procedures involving the upper (cheek) teeth, paranasal sinuses, maxilla and oral cavity (Newton et al 2000) and is achieved by local blocking the maxillary nerve within the pterygopalatine fossa (Bienert et al 2011). Rieder et al (2016) verified that the maxillary nerve block performed with the EFBI-technique is a feasible clinical technique and the present study demonstrated the practicability of the EFBI-technique under clinical conditions. Only four horses required additional nose-twitch to sedation for better performance of the local nerve block.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Desensitizing the maxillary branch of the trigeminal nerve is useful for surgical procedures involving the upper (cheek) teeth, paranasal sinuses, maxilla and oral cavity (Newton et al 2000) and is achieved by local blocking the maxillary nerve within the pterygopalatine fossa (Bienert et al 2011). Rieder et al (2016) verified that the maxillary nerve block performed with the EFBI-technique is a feasible clinical technique and the present study demonstrated the practicability of the EFBI-technique under clinical conditions. Only four horses required additional nose-twitch to sedation for better performance of the local nerve block.…”
supporting
confidence: 78%
“…Rieder et al (2016) confirmed in an experimental trail that the EFBI-technique is feasible. The results of this study indicated that a dose of 2 ml/100 kg BW lidocaine might be sufficient.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Concerning the region of the tooth structure to be removed, an infraorbital nerve block, which is associated with lower risks, was also considered. The choice to perform a maxillary nerve block was made with consideration of the acceptance by the horse and the difficulty of correct placement, and thus effectiveness of the nerve block (Tremaine 2007, Rieder et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Tetanus toxoid (Equip T, Zoetis Deutschland GmbH, Berlin, Germany; > 30 IU im) was administered prophylactically because the horse had received its last tetanus vaccination two years earlier. After positioning the horse in stocks and sedation, a maxillary nerve block within the pterygopalatine fossa was performed according to the instructions of Rieder et al (2016). Additionally, local anaesthesia of the gingiva and the periodontal space surrounding tooth 602 was performed using lidocaine (Lidocainhydrochlorid 2 %, Bela-pharm GmbH & Co. KG, Vechta, Germany).…”
Section: Treatmentmentioning
confidence: 99%